Assessing the influence of mechanical ventilation on blood gases and blood pressure in rattlesnakes - Bertelsen, Mads F. [UNESP]; Buchanan, Rasmus [UNESP]; Jensen, Heidi M. [UNESP]; Leite, Cleo A. C. [UNESP]; Abe, Augusto S. [UNESP]; Nielsen, Soren S.; Wang, Tobias [UNESP] (Wiley-Blackwell, 2015)
ObjectiveTo characterize the impact of mechanical positive pressure ventilation on heart rate (HR), arterial blood pressure, blood gases, lactate, glucose, sodium, potassium and calcium concentrations in rattlesnakes during anesthesia and the subsequent recovery period.Study designProspective, randomized trial.AnimalsTwenty one fasted adult South American rattlesnakes (Crotalus durissus terrificus).MethodsSnakes were anesthetized with propofol (15mgkg(-1)) intravenously, endotracheally intubated and assigned to one of four ventilation regimens: Spontaneous ventilation, or mechanical ventilation at a tidal volume of 30mLkg(-1) at 1 breath every 90seconds, 5 breaths minute(-1), or 15 breaths minute(-1). Arterial blood was collected from indwelling catheters at 30, 40, and 60minutes and 2, 6, and 24hours following induction of anesthesia and analyzed for pH, PaO2, PaCO2, and selected variables. Mean arterial blood pressure (MAP) and HR were recorded at 30, 40, 60minutes and 24hours.ResultsSpontaneous ventilation and 1 breath every 90seconds resulted in a mild hypercapnia (PaCO2 22.44.3mmHg [3.0 +/- 0.6 kPa] and 24.5 +/- 1.6 mmHg [3.3 +/- 0.2 kPa], respectively), 5breaths minute(-1) resulted in normocapnia (14.2 +/- 2.7 mmHg [1.9 +/- 0.4 kPa]), while 15breathsminute(-1) caused marked hypocapnia (8.2 +/- 2.5 mmHg [1.1 +/- 0.3kPa]). Following recovery, blood gases of the four groups were similar from 2hours. Anesthesia, independent of ventilation was associated with significantly elevated glucose, lactate and potassium concentrations compared to values at 24hours (p<0.0001). MAP increased significantly with increasing ventilation frequency (p<0.001). HR did not vary among regimens.Conclusions and clinical relevanceMechanical ventilation had a profound impact on blood gases and blood pressure. The results support the use of mechanical ventilation with a frequency of 1-2breathsminute(-1) at a tidal volume of 30mLkg(-1) during anesthesia in fasted snakes.
Keywords: Acid-base balance; Blood pressure; Crotalus durissus; Heart rate; Reptile; Ventilation